Functional Anatomy of the Mediastinal Lymph Nodes in Rats - Pasierbek, Michal (Mary Ann Liebert, Inc., 2014)
Background: The lymphatic system remains poorly recognized, yet for oncological reasons, it appears to be of great interest to both scientists and physicians. Methods and Results: Protocols were performed on 55 adult male Wistar rats. All procedures were conducted after intraperitoneal administration of 4% chloral hydrate and artificial ventilation. The observations of the rats' anatomy of lymphatic structures and observations of lymphatic drainage were conducted after injection of the tracer (ink suspension and/or 1% solution of fluorescein isothiocyanate dextran) into the thoracic wall, intraperitoneally, and into bile ducts, as well as after experimental cutting of the outflow of the lymph from the liver to the mediastinal lymph nodes. The author's own terminology was suggested: medial mediastinal lymph node and lateral mediastinal lymph node. The presence of the tracer was found in the mediastinal nodes after its injection into the posterior wall of the thoracic wall, intraperitoneally, and into bile ducts. After injection into bile ducts, the tracer was observed only in the left mediastinal nodes. After experimental cutting of the basic outflow of the lymph from the liver to the mediastinal nodes, the whole outflow took place through the thoracic duct to the left venous angle. Conclusions: 1. The locations of the lymph nodes in the thorax as well as the drainage area of those nodes are asymmetrical. 2. Left-sided nodes show larger range of drainage. 3. Cutting the basic lymph outflow from the liver to the mediastinal nodes stops immunological information being transferred to regional nodes of the liver situated in the mediastinum.